Epidemiology of track and field injuries - Edouard, P.; Alonso, J.-M. (New Studies in Athletics, 2013)
Injury is a cause of concern for all athletes - from amateurs at the recreational and grass roots levels to the elite professionals taking part in the IAAF World Championships in Athletics and the Olympic Games. Preventive measures, focused on the most relevant injuries (high frequency and/or severity), should be implemented in the preparation of the athlete with the aim of reducing future risk and/or severity of injury. Epidemiological data make it possible to identify and highlight the most relevant injuries, and thereby develop appropriate prevention strategies. The authors survey the existing literature focusing their attention on data linked to 1) injuries over the course of a season, 2) injuries at major championships and 3) injuries in young athletes. In addition to identifying the variations in injury risk in elite athletes by discipline and age, they point out that the data shows increased injury risk for young athletes. After calling for increased knowledge of injury incidence and characteristic in youth athletes, they conclude with identification of the main injury prevention strategies found in the literature.